Tingkat Keterampilan Teknik Dasar Smash dalam Permainan Bolavoli pada Mahasiswa Pendidikan Jasmani - Zen, Mohammad Zaim; Ma’arif, Ilmul; Prasetyo, Guntum Budi; Hidayat, Zakaria Wahyu (SPRINTER: Jurnal Ilmu Olahraga, 2024)
In this case it is known that the research objective is to determine the level of basic smash bolavoli technique skills, this study uses a survey method with tests and measurements to obtain actual data. The population is 75 physical education students, for the sampling method with total sampling every existing population is considered as a sample. The smash skill test tool is based on the target score in the field with five opportunities. data analysis methods using quantitative descriptive analysis and percentages. Based on the results of the smash skill test, data were obtained in the excellent category 0 (0%), good 39 (52%), moderate 31 (41.33%), less 5 (6.67%), and very less 0 (0%). So that by looking at the results of the study it is known that the conclusion of this study is that smash skills are in the good category.